RDNA-03. AUTOPHAGY AS A NOVEL THERAPEUTIC TARGET IN MUTANT IDH1 GLIOMAS. (11th November 2019) - Nunez, Felipe; Garcia-Fabiani, Maria; Kadiyala, Padma; Hong, Hanna; Comba, Andrea; Lyssiotis, Costas; Cheng, Shi-Yuan; Lowenstein, Pedro; Castro, Maria
Abstract: Mutated Isocitrate dehydrogenase 1 (IDH1 R132H ; mIDH1) is found in 50% of all adult gliomas and in 80% of lower-grade gliomas. IDH1 R132H promotes 2-hydroxyglutarate production which inhibits histone and DNA demethylases, inducing epigenetic reprogramming of the tumor transcriptome. We recently demonstrated that epigenetic reprogramming enhances DNA-damage response and confers radioresistance in mIDH1 glioma, harboring p53 and ATRX loss. Furthermore, several studies indicate that IDH1 R132H triggers cellular metabolism reprogramming. In this study, RNA-seq data revealed that mIDH1 glioma neurospheres (mIDH1-NS) have downregulated gene ontologies related to mitochondrial metabolism. Analysis of mitochondrial and glycolytic activity, using a Seahorse Analyzer, showed that mIDH1-NS have decreased levels of oxygen consumption and extracellular acidification rates, characteristic of quiescent state. Nevertheless, mIDH1 glioma cells can grow and generate tumors, suggesting that they might maintain self-renewal via autophagy. To investigate this hypothesis, we studied autophagy in wild-type and mIDH1 glioma cells analyzing LC3 conversion, p62 expression, and ULK1 protein phosphorylation. Mouse and human mIDH1 glioma cells exhibited increased expression of pULK1-S555, enhanced conversion of LC3I to LC3II, and decreased expression of p62, indicating that mIDH1 cells have an augmented autophagy. Also, key proteins involved in autophagy, including MST4 and UVRAG, are upregulated in mIDH1-NS. We also studied autophagy flux using LC3-mCherry-GFP reporter to identify LC3 recruitment at the autophagosome membranes and the autolysosome activity. Our results showed that mIDH1 cells have increased LC3 recruitment and enhanced autolysosome activity. Interestingly, autophagy has been related with glioma radioresistance. In our study, mouse and human mIDH1 glioma cells are sensitive to autophagy inhibition. In addition, autophagy inhibition restored radiosensitivity in mouse and human mIDH1 glioma cells, and in our mIDH1 glioma model, enhancing median survival compared with radiation alone. In conclusion, our results indicate that mIDH1 glioma cells maintain self-renewal via activation of autophagy, which represents a novel therapeutic target.